Nurturing Resilient Women: Single Parents from the Perspective of Islamic Education - Buto, Zulfikar Ali; Muhibuddin, Muhibuddin; Taufiq, Taufiq (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2025)
The phenomenon of single mothers is on the rise in modern society, bringing complex challenges in economic, psychological, social, and spiritual aspects. This article aims to examine the role and strength of women who live as single parents in educating their children based on Islamic educational principles. This research uses qualitative methods with Critical literature review to highlight the importance of spiritual education, moral strengthening, social skills development, life skills, and support from institutions and communities based on Islamic values. Based on a review of classical and contemporary Islamic educational literature, it was found that Islamic teachings give women a very noble position, especially as the main educators in the family environment, even without the presence of a spouse. Islam not only glorifies the role of mothers, but also emphasizes their pivotal role in shaping the character and personality of their children. The mental toughness, emotional independence, and spiritual intelligence of a single mother are formed through a comprehensive Islamic tarbiyah process, covering the spiritual, intellectual, and physical aspects. Through comprehensive education, women are able to raise a quality generation and build a just and civilized society. AbstrakFenomena ibu tunggal (single mother/parent) semakin meningkat di masyarakat modern, membawa tantangan kompleks dalam aspek ekonomi, psikologis, sosial, dan spiritual. Artikel ini bertujuan untuk mengkaji peran dan kekuatan perempuan yang hidup sebagai orang tua tunggal dalam mendidik anak-anak mereka berdasarkan prinsip-prinsip pendidikan Islam. Penelitian ini menggunakan metode kualitatif dengan tinjauan literatur kritis untuk menyoroti pentingnya pendidikan spiritual, penguatan moral, pengembangan keterampilan sosial, keterampilan hidup, dan dukungan dari lembaga dan komunitas berdasarkan nilai-nilai Islam. Berdasarkan tinjauan kritis terhadap sumber tulisan ilmiah dibidang pendidikan Islam klasik maupun kontemporer, ditemukan bahwa ajaran Islam memberikan posisi yang sangat mulia bagi perempuan, terutama sebagai pendidik utama dalam lingkungan keluarga, bahkan tanpa kehadiran suami. Islam tidak hanya mengagungkan peran ibu, tetapi juga menekankan peran sentral mereka dalam membentuk karakter dan kepribadian anak-anak mereka. Ketahanan mental, kemandirian emosional, dan kecerdasan spiritual seorang ibu tunggal terbentuk melalui proses tarbiyah Islam yang komprehensif, mencakup aspek spiritual, intelektual, dan fisik. Melalui pendidikan yang komprehensif, perempuan mampu mendidik generasi berkualitas dan membangun masyarakat yang adil dan beradab.